Efektivitas Konseling Kelompok dalam Meningkatkan Psychological Well-Being Remaja di Lingkungan Pendidikan: Systematic Literature Review (SLR) - Faizatul Mumtaza; Muslikah Muslikah (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Psychological well-being among adolescents in educational settings is an essential aspect of supporting optimal individual development, particularly in coping with academic and social demands. However, the increasing levels of stress, anxiety, and emotional problems among students indicate that psychological well-being has not been fully achieved. The limited number of integrative studies examining group counseling in this context encourages researchers to investigate how effective group counseling is in improving psychological well-being among adolescents in educational settings (RQ1), and how group dynamics function in the implementation of group counseling to enhance psychological well-being (RQ2). The method used is a Systematic Literature Review (SLR) following the PRISMA model. The screening results identified nine relevant publications that met the inclusion criteria and were used as research data. The findings indicate that group counseling is effective in improving adolescents’ psychological well-being, as reflected in increased self-acceptance, autonomy, environmental mastery, positive relationships, purpose in life, and personal growth. Furthermore, group dynamics such as social support, open communication, and peer interaction play a crucial role in strengthening the effectiveness of the intervention. Group counseling services can be optimized by enhancing supportive group interactions and selecting appropriate counseling approaches based on students needs.